Idiopathic Fascicular Left Ventricular Tachycardia: A Case Report - Kadek Agus Putra Udayana; I Putu Parwata Jaya (Cermin Dunia Kedokteran, 2020)
Idiopathic fascicular left ventricular tachycardia (IFLVT) is the most common idiopathic ventricular tachycardia (IVT) of the left ventricle. ILFVT is characterized by right bundle branch block and left axis deviation. We report a case of IFLVT in a 34-year-old woman presenting with palpitation. The ECG revealed a wide QRS complex tachycardia with a right bundle branch block (RBBB) and right axis deviation. Vagal maneuvers were ineffective. Conversion to sinus rhythm was obtained 10 hours later, with i.v amiodarone. The patient was discharged after 3 days on oral verapamil. Idiopathic Fascicular Left Ventricular Tachycardia (IFLVT) adalah bentuk paling sering Idiopathic Ventricular Tachycardia (IVT) ventrikel kiri. ILFVT ditandai dengan blok cabang berkas kanan dan penyimpangan sumbu ke kiri. Kami melaporkan kasus IFLVT pada wanita 34 tahun yang mengalami palpitasi. EKG menunjukkan takikardi kompleks QRS lebar dengan morfologi blok cabang berkas kanan dan penyimpangan sumbu ke kanan. Manuver vagal tidak efektif. Konversi ke irama sinus diperoleh 10 jam kemudian dengan amiodaron i.v.. Pasien dipulangkan setelah 3 hari dengan verapamil oral.